OPTIMIZATION OF THE NUMBER OF VISCOELASTIC DAMPERS (VED) AND INITIAL COST OF A 30-STORY REINFORCED CONCRETE STRUCTURE WITH VED USING GAUSSIAN PROCESS REGRESSION (GPR) - Pradipta Mulya, Anggadiawan
In Indonesia, the earthquake-resistant structural system that is often used is a structural system that tends to be conventional, namely by dissipating earthquake energy in structural elements. The conventional structural system that is often used in buildings in Indonesia is a dual system with special reinforced concrete shear walls . Meanwhile, structural systems that tend to be modern are structural systems that can reduce earthquake energy dissipation in structural elements by using additional devices whose function is to absorb earthquake energy. In Indonesia there are still very few buildings using modern structural systems. One of the reasons obtained from the Sumitomo Rubber Industries team who conducted a survey in Indonesia is that building owners in Indonesia are more concerned with initial costs than the life cycle costs of a building. Therefore, it is necessary to know the comparison of the initial cost of structures with dampers with conventional structures. So to find out the initial cost of a structure with dampers will require a lot of trial-and-error on the combination of the number of dampers on each floor needed. So in this thesis machine learning with Gaussian process regression (GPR) is used to find out the optimum amount of VED which produces the cheapest price but still meets existing requirements. The required parameters that must be met from the data set for structures with dampers are the ratio of drift between floors and device displacement. That's the only parameter because the structure meets the strength requirements but does not meet the drift ratio requirements between floors. Analysis of structures with dampers is carried out using the fast nonlinear analysis (FNA) method, which has relatively faster computing times than nonlinear time history analysis (NLTHA), but the FNA optimization results will still be checked with NLTHA. Therefore, in this thesis research, a 30-story reinforced concrete structure with viscoelastic dampers (VED) was used as a damping device which was analyzed using FNA and optimized with GPR and compared with the initial cost of a structure with double system shear walls. The research results show that the FNA inter-floor deviation ratio is smaller than NLTHA on floors that use VED, while on floors that do not use VED, the FNA interfloor deviation ratio is greater than FNA. Meanwhile, on average, FNA device displacement has a device displacement value that is greater than NLTHA, except for the lower floors, FNA is smaller than NLTHA. Furthermore, optimization with GPR also produces the lowest costs among the combinations in other data sets and also produces cheaper costs compared to structures with shear walls.